2019
DOI: 10.1021/acs.jpcc.9b03808
|View full text |Cite
|
Sign up to set email alerts
|

The Role and Control of Residual Bulk Oxygen in the Catalytic Growth of 2D Materials

Abstract: We systematically study the effects of residual oxygen in the bulk of Cu foil catalysts on the chemical vapour deposition (CVD) of graphene. While oxidation is widely used to remove impurities in metal catalysts and to control the nucleation density of graphene, we show that minute concentrations of residual bulk oxygen can significantly deteriorate the quality of as-grown graphene highlighted by an increased Raman D/G ratio, increased propensity to post-growth etching and increased fraction of multi-layer gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 80 publications
1
39
0
Order By: Relevance
“…However, holes and damage often occur for such conditions. This observation parallels with our previous studies of bulk oxygen effects for Cu catalysed graphene growth 35 , where higher defect densities were confirmed with Raman spectroscopy and increased postgrowth etching in H2. We find that the effect of Fe oxidation can be nullified (in terms of the h-BN material outcome) if a prolonged reducing (NH3) atmosphere is used from the start (gas 1) or with the addition of a sufficient C2H2 dose with a shorter NH3 annealing ( Supplementary Figures S5c,d).…”
Section: Pre-growth Conditioning Of Fe Foils Towards Large Monolayer supporting
confidence: 91%
See 1 more Smart Citation
“…However, holes and damage often occur for such conditions. This observation parallels with our previous studies of bulk oxygen effects for Cu catalysed graphene growth 35 , where higher defect densities were confirmed with Raman spectroscopy and increased postgrowth etching in H2. We find that the effect of Fe oxidation can be nullified (in terms of the h-BN material outcome) if a prolonged reducing (NH3) atmosphere is used from the start (gas 1) or with the addition of a sufficient C2H2 dose with a shorter NH3 annealing ( Supplementary Figures S5c,d).…”
Section: Pre-growth Conditioning Of Fe Foils Towards Large Monolayer supporting
confidence: 91%
“…Graphene was grown by CVD on Cu foils (Alfa Aesar, 99.8 %, 25 µm) in a custom tube furnace system using previously reported methods 35,40 . Briefly, oxidised Cu foils were loaded in the CVD system and annealed at 1070 °C in 50 mbar Ar, followed by a Ar, H2, CH4 gas mixture for the growth stage, with flow rates of 583 sccm, 17 sccm and 0.013 sccm respectively for 5 hours to obtain continuous graphene films with mm-sized domains.…”
Section: Graphene Heterostructure Fabrication With H-bn and Al2o3 Andmentioning
confidence: 99%
“…Graphene was grown by introducing a CH 4 /H 2 /Ar mixture (1.2 × 10 -2 , 9, and 41 mbar, respectively) for 6 h. Monolayer hBN was grown by CVD on Fe foils as described in prior work. [47][48][49] Briefly, 0.1 mm Fe foils (99.8% purity) were oxidized in air at 350 °C for 5 min, followed by annealing in 1 × 10 -2 mbar Ar at 980 °C for 20 min to remove localized impurities in the foil and create a minute oxygen reservoir. A brief reducing treatment of 3 × 10 −3 mbar acetylene was applied for 5 min, followed by a 20 min dose of ammonia at 1 × 10 -2 mbar.…”
Section: Methodsmentioning
confidence: 99%
“…The in‐house growth was performed as follows: Continuous monolayer graphene films consisting of mm‐sized domains were grown by CVD on Cu foils. [ 47 ] Briefly, Cu foils (99.9%) were oxidized in air at 250 °C for 5 min, followed by annealing in Ar (50 mbar, 30 min), and subsequently by H 2 annealing (12 mbar H 2 , 38 mbar Ar, 60 min) at around 1075 °C. Graphene was grown by introducing a CH 4 /H 2 /Ar mixture (1.2 × 10 –2 , 9, and 41 mbar, respectively) for 6 h. Monolayer hBN was grown by CVD on Fe foils as described in prior work.…”
Section: Methodsmentioning
confidence: 99%
“…[ 26 ] More generally surface oxidation is also known to be of critical importance for the CVD growth of 2D materials. [ 27 ] To probe experimentally the degree of surface oxidation for individual Ni grains we performed an annealing process of the Ni foil, identical to that used prior to growth, but instead of performing hBN growth we instead analyzed the pre‐growth surface oxidation levels on individual Ni grains by correlating EBSD mapping with elemental mapping via energy dispersive X‐Ray spectroscopy (EDS). We observed that the concentration of oxygen on (001) grains is significantly reduced compared to those on (101) or (001) grains, suggesting that diffusion will be enhanced on (001) Ni grains, see Supporting Information.…”
Section: Figurementioning
confidence: 99%